2019
DOI: 10.1186/s12864-019-5486-7
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly of Persea americana cv. ‘Hass’ transcriptome during fruit development

Abstract: BackgroundAvocado (Persea americana Mill.) is a basal angiosperm from the Lauraceae family. This species has a diploid genome with an approximated size of ~ 920 Mbp and produces a climacteric, fleshy and oily fruit. The flowering and fruit set are particularly prolonged processes, lasting between one to three months, generating important differences in physiological ages of the fruit within the same tree. So far there is no detailed genomic information regarding this species, being the cultivar ‘Hass’ especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…In this study, 93.82% (71,627 of 76,345) of the nonredundant transcripts were annotated based on similarities with sequences in public databases. Thus, a greater proportion of transcripts were annotated in this study than in previous investigations involving NGS data for various avocado races (49.00%) [18] and for avocado mesocarp samples (57.50%) [55]. We determined that the mean length of the avocado nonredundant transcripts was2330 bp, implying that our sequences were long enough to represent full-length transcripts.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this study, 93.82% (71,627 of 76,345) of the nonredundant transcripts were annotated based on similarities with sequences in public databases. Thus, a greater proportion of transcripts were annotated in this study than in previous investigations involving NGS data for various avocado races (49.00%) [18] and for avocado mesocarp samples (57.50%) [55]. We determined that the mean length of the avocado nonredundant transcripts was2330 bp, implying that our sequences were long enough to represent full-length transcripts.…”
Section: Discussionmentioning
confidence: 73%
“…Transcriptome sequencing is a useful technique for obtaining a large number of transcripts for organisms lacking a reference sequence, at least partly because it is inexpensive and can be completed rapidly [51][52][53]. To date, several short-read next-generation sequencing (NGS) transcriptome databases have been developed for avocado mesocarp samples [54,55] and avocado mixed tissue samples [18,56]. However, both the number and length of the transcript sequences derived from these short-read NGS studies have hamperedtheirapplication ingenetics and molecular biology research [41].…”
Section: Discussionmentioning
confidence: 99%
“…De novo assembly of avocado cv. "Hass" transcriptome during mesocarp development was conducted and identified tissue-specific regulation and biosynthesis of TAG, respectively [7,8]. Moreover, the transcriptomes of aerial buds, leaves, flowers, stems, seeds, and roots from an unknown Mexican accession were determined using different sequencing platforms, and it revealed strong differences in gene expression patterns between different organs [6].…”
Section: Discussionmentioning
confidence: 99%
“…Many commercial avocado accessions are thus often natural or artificial hybrids [5]. The only available transcriptome data, to our knowledge, is that of the Hass cultivar, classified as a Guatemalan × Mexican hybrid, and an unknown Mexican accession [6][7][8], which extremely restricts genetic and breeding studies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that at early stages of fruit set in avocado, about 44% of the flesh weight is due to sugars which continue to increase during rapid fruit growth but then decline during oil accumulation (Liu et al, 1999b). One fourth of total oil content accumulation in avocado has been reported to occur during early stages of development and Vergara-Pulgar et al (2019) have recently reported enrichment of transcripts related to lipid localization, fatty acid synthase activity and acyl carrier activity involved in fatty acid biosynthesis when comparing mesocarp of 150 DAFS (days after fruit set) with 240 DAFS, respectively. Acetyl-CoA carboxylase the regulatory enzyme that controls the rate of fatty acid synthesis and catalyzes the first reaction to generate malonyl-CoA was also detected in avocado and oil palm (Dussert et al, 2013; Kilaru et al, 2015).…”
Section: Lipid Metabolism During Avocado Fruit Growth Development Anmentioning
confidence: 99%